Integrated Metabolomic and Transcriptomic Analysis and Identification of Dammarenediol-II Synthase Involved in Saponin Biosynthesis in Gynostemma longipes - Ye, Shuang; Feng, Lei; Zhang, Shiyu; Lu, Yingchun; Xiang, Guisheng; Nian, Bo; Wang, Qian; Zhang, Shuangyan; Song, Wanling; Yang, Ling; Liu, Xiangyu; Feng, Baowen; et al. (Frontiers in Plant Science, 2022)
Gynostemma longipes contains abundant dammarane-type ginsenoside and gypenosides that present extensive pharmacological activities. Increasing attentions has been paid to elucidation of CYPs and UGTs which participated in ginsenoside downstream biosynthesis in Panax genus in the past decade. However, the information on OSCs, the upstream genes responsible for different skeleton biosynthesis of ginsenoside and gypenosides were rare reported. Here, the integrative study of metabolome and transcriptome in leaf, stolon and rattan was conducted and the function of GlOSC1 was demonstrated. A total of 46 triterpenes were detected and highly abundance in stolon, whereas genes expression analysis indicated that up-stream OSC genes which were responsible for saponin skeleton biosynthesis are highly expressed in leaf. This result indicated the skeleton of saponin was mainly biosynthesized in leaf by OSCs, subsequently transferred to stolon via CYPs and UGTs biosynthesis to form various ginsenoside and gypenosides. Additionally, a new dammarane-II synthase (DDS), GlOSC1 was identified based on bioinformatics analysis, yeast expression and enzyme assay. The result of LC-MS proved that GlOSC1 could catalyze 2,3-oxidosqualene to form dammarenediol-II via cyclization. This frame of work uncovered the biosynthetic mechanism of dammarenediol-II, the important starting substrate for ginsenoside and gypenosides biosynthesis, could be applied for increasing yield of valuable ginsenoside and gypenosides under excessive substrate in yeast cell factory through synthetic biology strategy.